PENERAPAN VIDEO PEMBELAJARAN SEBAGAI ALTERNATIF MEDIA PEMBELAJARAN BAHASA INGGRIS DI MA YASPI KELAS X DAN XI PADA MASA PANDEMI COVID 19 - Rahmania Anida; Ramdhaniyah Arifa Suci; Ikhwandi Muhamad Ripin (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
Learning management originates from managing how learning continues effectively and efficiently. Various learning media are designed in such a way according to the curriculum that will be applied for students. The teacher is a learning facilitator for students who lead to distributing acceptable material according to the characteristics of students learning styles. It is inseparable from the learning media. The problem is, during the epidemic, teaching and learning activities carry out remotely or online. This study uses a qualitative approach. The author uses data collection methods in the form of interviews, observations, and documentation. The results of this study indicate the innovation of learning media in the form of educational videos that can use as a means of support. This educational video is an innovation of learning media during the epidemic and considered more effective and efficient because students do not have books are like textbooks at school. Educational videos are said to be one of the solutions to the lack of supporting facilities when students study from home because during the epidemic the school has not allowed students to borrow books directly. Making this educational video uses an easy-to-find editing application so it doesn't make it difficult for teachers to make it. This learning video display is present and distributed to students via WhatsApp groups. Discussion of videos through WhatsApp groups is considered more effective, and students can save videos permanently after downloading without internet access again. Keywords: Epidemic, Learning, Media References Awwaabiin, Salmaa. “Metode Penelitian Kualitatif: Pengertian Menurut Ahli, Jenis-Jenis, Dan Karakteristiknya.” Deepublish (Blog), 2021. Https://Penerbitdeepublish.Com/Metode-Penelitian-Kualitatif/. Elisa, Edi. “Pengertian Pembelajaran.” Artikel. Education Channel Indonesia (Blog), 2016. Https://Educhannel.Id/Blog/Artikel/Pengertian-Pembelajaran.Html. Haq, Fath. “Manajemen Pembelajaran Peserta Didik Saat Pandemi Covid-19.” Kompasiana (Blog), 2020. Https://Www.Kompasiana.Com/Fathhaq6491/5f38aae4097f361c7f12ebf2/Manajemen-Pembelajaran-Peserta-Didik-Saat-Pandemi-Covid-19. Hilwiyah, Wiwi. “Pengertian Manajemen Pembelajaran.” Academia, N.D. Https://Www.Academia.Edu/10500962/Pengertian_Manajemen_Pembelajaran#: :Text=Pengertian%20manajemen%20pembelajaran%20manajemen%20pembelajaran%20adalah%20segala%20usaha,Tercapainya%20proses%20belajar%20mengajar%20yang%20efektif%20dan%20efisien. Om.Makplus. “Pengertian Manajemen Serta Pengertian Menurut Ahli.” Definisi Dan Pengertian Menurut Ahli (Blog), 2015. Http://Www.Definisi-Pengertian.Com/2015/06/Definisi-Manajemen-Pengertian-Menurut-Ahli.Html. Dosen Pendidikan. “Pengertian Pembelajaran Menurut Para Ahli,” 2021. Https://Www.Dosenpendidikan.Co.Id/Pengertian-Pembelajaran-Menurut-Para-Ahli/. Prawiro, M. “Pengertian Manajemen: Fungsi, Unsur, Dan Tujuan Manajemen Dalam Organisasi.” Maxmanroe.Com (Blog), 2021. Https://Www.Maxmanroe.Com/Vid/Manajemen/Pengertian-Manajemen.Html. Rijali, Ahmad. “Analisis Data Kualitatif” 17 (2018). Http://Jurnal.Uin-Antasari.Ac.Id/Index.Php/Alhadharah/Article/View/2374. Saifullah, Munir Ahmad, And Mohammad Darwis. “Manajemen Pembelajaran Dalam Meningkatkan Efektivitas Proses Belajar Mengajar Di Masa Pandemi Covid-19” 3, No. 2 (2020). Manajemen Pembelajaran Dalam Meningkatkan Efektivitas Proses Belajar Mengajar Di Masa Pandemi Covid-19.